(untitled) (International Journal of Physiotherapy, 2017)
Background: Research reports had noted an apparent increase in cutaneous and deep blood flow as a result of low-intensity laser therapy (LLLT) in normal subjects. The purpose of te study was to investigate the effective laser pulse frequency either (200 or 2000 Hz) on improving blood flow in type 2 diabetic patients. Forty-five diabetic patients selected from out clinic of Kasr El-Aini Hospital, Cairo University assigned randomly into three groups. The blood flow volume, blood flow velocity and caliper of the blood vessel were evaluated before laser application and after twelve sessions using duplex Doppler ultrasound. Methods: Combined He-Ne and infrared LILT was administered three times a week for twelve sessions at intensity of 3 J, power 500 mW, 808 nm duration 15 min and pulse frequency 200 Hz for group I, 2000 Hz for group II, and sham LILT for group III on the sural artery at posterior aspect of dominant leg. Result: Paired t-test revealed that low pulse frequency (200 Hz) LILT produced significant improvement in blood flow volume and blood flow velocity (t= 1.76, p= 0.001 and t= 2.8, p= 0.01) respectively (P<0.05). While there was no significant changes in caliper of the blood vessel of group I, blood flow volume, blood flow velocity or caliper of the blood vessel of group II and group III (t= 2.15, p= 1, t= 2.15, p= 1, t= 1.11 p= 0.31, t= 1.54, p= 0.15, t= 2.51, p= 1, t= 1.21 p= 0.33, t= 1.45, p= 0.15) respectively (P<0.05). ANOVA test in between groups revealed insignificant changes in all pre and post- measures except significant results in blood flow volume and velocity which indicating the superiority of group I on both group II and III by post hoc test. Conclusion: low pulse frequency of LILT (200 Hz) could improve blood flow than high pulse frequency (2000 Hz).